To the question of the personality of Zhiroslav Nazhirovich who led the Kyiv troops to Mensk in 1159 - Nagirnyy, Vitaliy M. (Journal of the Belarusian State University. History, 2020)
The article deals with the biography of the Kyiv voivode Zhiroslav Nazhirovich. The boyar is mentioned in the Kyiv Chronicle only once, in 1159, when he leaded the military unit of Torks that had been by the Kyiv prince Rostislav Mstislavich to Mensk to help the Polotsk prince Rogvolod Borisovich. The author admits that Zhiroslav was born in the first third of the 12th century and could be the son of both Nazhir from the entourage of Vladimir Vsevolodovich Monomakh and Nazhir Pereyaslavich who served the Prince of Kyiv Izyaslav Davidovich. Based on the laconic data of the chronicles one can assume that Zhiroslav, although he yielded in status to other Kyiv voivodes, he had the considerable experience in military affairs. The further fate of Nazhirovich, after his returning from the Mensk campaign in 1159, is not analyzed in the sources. His possible descendants can be the Trepolsky sergeant Sdeslav Zhiroslavich and the Kyiv voivode Daniil Zhirovich (Nazhirovich).